Review of Islamic Aqidah in Represented Marriages : Case Study at KUA Mahato Village, North Tambusai District, Rokan Hulu Regency - Sari Pane, Elma (Yayasan Salam Cerdas Al-Fattah, 2023)
Wedding practices Based on Islamic law, the role of marriage guardian has undeniable significance, especially in the context of the prospective bride's marriage. The concept of marriage guardians divides the roles between lineage guardians and judge guardians, with the order of priority determined by the family relationship with the prospective bride. However, in situations where the guardian of the line is not present, cannot be present, or refuses to carry out his duties, the role of the guardian of the judge becomes important. The guardian judge acts as a substitute for the guardian of nasab and can take over the responsibilities of the guardian of marriage, especially after a religious court decision regarding the guardian of adhal or who refuses to carry out his duties. This study uses a descriptive analytical approach to investigate the concept and practice of marriage guardians in marriages based on Islamic law. Data was obtained from Islamic legal literature, related laws and regulations, as well as the views of Islamic scholars and legal experts. This article analyzes the regulations regarding marriage guardians in Islamic law, highlighting the importance of protecting the prospective bride and how these regulations provide a clear framework for carrying out the marriage process in accordance with Islamic principles.